Determinants of Market Integration and Price Transmission in Indonesia - Varela, Gonzalo (World Bank, Washington, DC, 2012)
This paper investigates the determinants of price differences and market integration among Indonesian provinces, using data from retail cooking oil, rice and sugar markets during the period 1993-2007, and from wholesale maize and soybean markets during the period 1992-2006. The authors measure the degree of integration using co-integration techniques, and calculate average price differences. They use regression analysis to understand the drivers of price differences and market integration. For rice and sugar, they find wide market integration and low price differences, in the range of 5-12 percent. For maize, soybeans and cooking oil, they find less integration and higher price differences (16-22 percent). Integration across provinces is explained by the remoteness and quality of transport infrastructure of a province. Price differences across provinces respond to differences in provincial characteristics such as remoteness, transport infrastructure, output of the commodity, land productivity and income per capita.